Cycle-based high-intensity sprint exercise elicits acute cognitive dysfunction in psychomotor and memory task performance - Dufner, Trevor J.; Moon, Jessica M.; Wells, Adam J. (Frontiers in Cognition, 2024)
Purpose: To examine the impact of an acute high-intensity sprint exercise protocol (HISEP) for eliciting postexercise cognitive dysfunction in psychomotor, attentional, executive, and memory tasks. Methods: Twenty-four recreationally active adults (22±4yrs, 169.39±10.07cm, 75.80±14.73kg, 27.03±9.55BF%) performed a HISEP on a cycle ergometer. Average psychomotor reaction time (avgRT; Dynavision D2 Mode A & Mode B), mood (Profile of Mood States Questionnaire; POMS), and cognition (Automated Neuropsychological Assessment Metrics; ANAM) were assessed pre-(PRE), post-(POST) and 60-minutes post (60POST) HISEP. One-way repeated measuresANOVAs were used to assess changes across time. Results: Fatigue (main effect: p<0.001, ηp 2 =0.309) was significantly higher at POST compared to PRE (p=0.007). Tension (main effect: p=0.021, ηp 2 =0.154) was significantly lower at 60POST compared to PRE (p=0.029). Mode A avgRT (main effect: p=0.022, ηp 2 =0.153) was significantly slower at POST compared to PRE (p=0.026). Throughput (TP) scores for ANAM code substitutiondelayed (CSD) task (main effect: p<0.001, ηp 2 =.284) and matching to sample (M2S) tasks (main effect: p=0.014,ηp 2 =0.169) were significantly lower at POST compared to PRE (p=0.001 and p=0.025, respectively), while mathematical processing (main effect: p=0.002, ηp 2 =0.232) was significantly higher at 60POST compared to both PRE (p=0.019) and POST (p=0.005). No other significant changes in cognitive task performance were observed (p's>0.05). Conclusions: The HISEP is a feasible and time-effective fatiguing exercise stimulus capable of eliciting acute cognitive dysfunction in psychomotor and memory task performance. NCT05100589